Relationship of low serum 25 (OH) Vitamin D and dementia – A cross-sectional observational study from a neurology teaching hospital in East India: Relationship of low serum 25 (OH) Vitamin D and dementia in East India - Misra, Amar Kumar; Bhattacharjee, Annesh; Mukherjee, Joydeep; Kumar, Sanjay; Mohanty, Bijendra (Asian Journal of Medical Sciences, 2022)
Background: In view of the rapidly growing number of aged population with dementia in India, widespread hypovitaminosis D in the elderly individual, high frequency of dementia of unknown etiology, many studies showing a definite role of Vitamin D in dementia as well as some of the literature showing inconsistent results and reverse causality of hypovitaminosis D in dementia, we planned to investigate the relation between low vitamin D and risk of dementia. Aims and Objective: The aim of the current study was to find out any relationship of Vitamin D with dementia. Materials and Methods: This cross-sectional observational study was performed at a neurology-teaching hospital, Kolkata, India. Ethical clearance was obtained from the hospital ethics committee. A total of fifty adults completed interviews on a semi-structured questionnaire. In addition, general medical and neurological examination and detailed cognitive assessment, including MMSE, were carried out after taking written consent. All individuals with dementia, and age-gender-matched healthy volunteers provided blood samples for routine and relevant biochemical examination, including the estimation of serum 25(OH) Vitamin D by Chemiluminescence Immuno Assay (CLIA). In addition, appropriate statistical methods were applied to analyse the results. Results: Overall, ninety percent of participants had low serum 25(OH)Vitamin D, defined as 25(OH)D < 20mg/ml. Hypovitaminosis D was associated with early and late-stage dementia and was statistically significant. Only five individuals were found to have sufficient 25 (OH) Vitamin D. Conclusion: The mean vitamin D level of demented patients was significantly lower compared to the control population. Our observations provide an association between Vitamin D deficiency and dementia and provides a background of longitudinal prospective study in future to show cause and effect relationship between dementia and hypovitaminosis D.